Analysis of student dropout and factors associated with student permanence in a Peruvian university - Sánchez-Hernández, Guillermo (2017)
ABSTRACT This article aimed to analyze student dropout and factors associated with the permanence of students enrolled in the first cycles at the Universidad Privada del Norte (UPN), Trujillo campus (Peru), during the academic period between 2008 and 2012. To this effect, a Service Satisfaction Survey (SSS) was applied, as well as information was collected from the enrollment unit. The data analysis consisted of calculating the Semiannual Desertion Index (SDI) and assessing the relationship among different factors of the SSS. The results revealed an annual increase in SDI. Student permanence is predicted based on student satisfaction, by guaranteeing academic and infrastructure quality. It is concluded that student dropout has negative consequences for the institution; it is necessary, therefore, to identify other factors that predict student retention.